Investigation of the effect of radiotherapy on the proliferative ındex (ki-67) in recurring diffuse glial tumors - (:unkn) unknown (My University, 2011)
Giriş: Radyoterapinin (RT) apopitozu uyarması, mitoz inhibisyonu, mutajen etki, kromozomal aberasyon, neoplastik transformasyon gibi birtakım etkileri vardır. Amaç: Bu çalışmada diffüz glial tümörlerde uygulanan RT\'nin tümörün proliferatif aktivitesi ve mitotik aktivitesinin üzerine etkisinin araştırılması amaçlanmıştır. Materyal-Metod: Glial tümör tanısı almış ve nüksleri nedeniyle tekrar opere olmuş (RT alan ve almayan) 49 olgu çalışmaya alınmıştır. Araştırılan tümör grubunu diffüz astrositoma, oligodentroglioma ve oligoastrositomalar oluşturmaktadır. Olgular primer ve nüks tümörlerinin tanıları bilinmeksizin tekrar değerlendirilmiş ve grade\'lendirilmiştir. Olguların tümüne Ki-67 immünhistokimyası uygulanmıştır. Sonuç: Nüks tümörlerde radyoterapi alan grupta grade ve Ki-67 proliferasyon indeksi daha düşük bulunmuştur. Ayrıca RT alan grupta mitotik aktivitenin baskılandığı gösterilmiştir.

Introduction: Radiotherapy (RT) has various effects such as apoptosis stimulation, mitosis inhibition, mutagenic effect, chromosomal aberration and neoplastic transformation. Aim: The aim of this study was to investigate the effect of RT administered to diffuse glial tumors on the proliferation activity and mitotic activity of the tumor. Material-Method: An overall of 49 re-operated recurrent cases (16 cases had received postoperative RT while 33 cases did not receive RT) diagnosed as glial tumor were included in this study. The tumor cohort consisted of diffuse astrocytoma, oligodendroglioma and oligoastrocytomas. Ki-67 proliferating index, mitoses and grades of the primary and recurrent tumors were compared. Result: We found that the grades of recurrent tumors were lower than the grade during the first surgery in cases that had RT compared to those that had not. Similarly, Ki-67 was lower in cases that had received RT. We also noted suppressed mitotic activity in cases that had received RT.
Nüks gösteren diffüz glial tümörlerde radyoterapinin proliferatif indeks (ki-67) üzerine etkisinin araştırılması
Keywords: Nörolojik Bilimler